2022
DOI: 10.54034/mic.e1295
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Salmonella enterica serovar Typhi strain from a young Brazilian patient: the relevance of automated microbiological methods for the rapid diagnosis of systemic infections

Abstract: Introduction: Latin American countries have public health problems that are aggravated by inadequate basic sanitary conditions. Inefficient vaccination coverage, as well as the fact that a significant portion of the population is exposed to contaminated water and food, can lead to an increase in the incidence of some diseases. Methodology: the work reports a case of infection by Salmonella enterica serovar Typhi (S. Typhi), whose contagion is strictly related to personal and environmental hygiene conditions. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…We would like to share ideas on the publications regarding "Identification of Salmonella enterica serovar Typhi strain from a young Brazilian patient: the relevance of automated microbiological methods for the rapid diagnosis of systemic infections (1)." Batista-Araújo et al concluded that "accurate identification and immediate detection of the etiologic agent using automated methods... (1)" We agree that the automated tool might be helpful for diagnosis of bacterial infection.…”
Section: Dear Editormentioning
confidence: 99%
“…We would like to share ideas on the publications regarding "Identification of Salmonella enterica serovar Typhi strain from a young Brazilian patient: the relevance of automated microbiological methods for the rapid diagnosis of systemic infections (1)." Batista-Araújo et al concluded that "accurate identification and immediate detection of the etiologic agent using automated methods... (1)" We agree that the automated tool might be helpful for diagnosis of bacterial infection.…”
Section: Dear Editormentioning
confidence: 99%
“…We recently received a letter to the editor (1) about our recent clinical case published in this journal (2). The public health problems faced in Brazil and other Latin American countries are recurrent and involve multiple causes.…”
mentioning
confidence: 99%
“…The present study didn´t aim to describe the disease itself, a knowledge widely described in the medical literature, not even to make an overview of public health, because is not our primary activity area, we also didn´t intend to evaluate the performance of automated diagnostic, since we are facing a clinical case (2).…”
mentioning
confidence: 99%